Non-Vitamin K Antagonist Oral Anticoagulants A Concise Guide - Shantsila, Eduard; Lip, Gregory YH (Springer International Publishing : Imprint: Adis, 2016)
This book is an essential guide to the medical treatment of thrombosis and presents core principles of anticoagulant therapeutics as well as drug recommendations. Written by recognized experts in the field, this concise, accessible handbook provides a unique and valuable resource in the cardiovascular field, both for those currently in training, and for those already in clinical or research practice.  .